Early‐Life Sugar Consumption Affects the Microbiome in Juvenile Mice - Reem Moath Alasmar (14778949) (2023)
Scope The composition of the gut microbiota is influenced by the dietary nutrient. Sugar has been linked with many metabolic health disorders such as heart disease, metabolic syndrome, and immune disorders. Long-term consumption of sugar influences the landscape of gut microbiota by altering the gut microbial population called dysbiosis. This study aims to evaluate the impact of long-term consumption of high sugar diet (HSD) on the diversity of gut microbiota. Methods and results CD1 mice are given high concentration of sugar for 15 weeks followed by a recovery period of 10 weeks. Real-time polymerase chain reaction and 16S rRNA next-generation sequencing methods employ to identify microbiome diversity. The results show that Firmicutes and Bacteroidetes are the predominant phyla in control, cecum, and fecal samples. Firmicutes population are gradually increased in treated samples even after the recovery period, whereas Bacteroidetes abundance slightly reduces throughout the study. Conclusion The present study shows that the impact of long period of high sugar diet consumption alters the diversity of normal gut flora which can be restored after 10 weeks of sugar withdrawal. This indicates that the intervention of healthy and nutritious diet influences gut microbes and this can be beneficial in reducing the implication of early life metabolic disorders such as obesity. Other Information Published in: Molecular Nutrition & Food Research License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/mnfr.202200322